2015
DOI: 10.3390/molecules200916419
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antibacterial and Antitubercular Activities of Some 5H-Thiazolo[3,2-a]pyrimidin-5-ones and Sulfonic Acid Derivatives

Abstract: A series of 5H-thiazolo[3,2-a]pyrimidin-5-ones were synthesized by the cyclization reactions of S-alkylated derivatives in concentrated H2SO4. Upon treatment of S-alkylated derivatives at different temperatures, intramolecular cyclization to 7-(substituted phenylamino)-5H-thiazolo[3,2-a]pyrimidin-5-ones or sulfonation of cyclized products to sulfonic acid derivatives occurred. The structures of the target compounds were confirmed by IR, 1 H-NMR, 13 C-NMR and HRMS studies. The compounds were evaluated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Thiation of 15 with P 4 S 10 in dioxane‐DMF at 120°C afforded the 2,4‐dithiolumazine analogues 16 (64%). Recently, Cai et al reported that S ‐alkylation of substituted 2‐thiouracil analogues proceeded smoothly with indication that the tautomeric hydrogen was found to favor N3 rather than N1. Thus, alkylation of 15 with phenacyl chloride and its 4‐methoxy analogue gave the S ‐alkyl‐pteridine derivatives 18 and 19 in 78% and 74% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thiation of 15 with P 4 S 10 in dioxane‐DMF at 120°C afforded the 2,4‐dithiolumazine analogues 16 (64%). Recently, Cai et al reported that S ‐alkylation of substituted 2‐thiouracil analogues proceeded smoothly with indication that the tautomeric hydrogen was found to favor N3 rather than N1. Thus, alkylation of 15 with phenacyl chloride and its 4‐methoxy analogue gave the S ‐alkyl‐pteridine derivatives 18 and 19 in 78% and 74% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Various thiazolopyridines have been synthesised via various synthetic methods and many derivatives have shown interesting biological applications [3,4]. The asymmetric unit of the crystal structure of the title compound consists of two independent molecules of C 13 H 10 N 2 OS.…”
Section: Discussionmentioning
confidence: 99%
“…NA5 displayed a remarkable potency against not only H37Rv but also the susceptible as well as the multidrug-resistant clinical isolates superior to isoniazid (15). Moreover, thiazolopyrimidines have also received significant attention as antimycobacterial agents due to their resemblance to purine (16). Encouraged by these observations, we have continued our research on heterocyclic compounds (17,18).…”
mentioning
confidence: 95%